Laryngeal Mask Airway Does Not Reduce Postoperative Nasal Bleeding Outside the Operation Room after Intranasal Surgery. (28th November 2013) - Zhang, Xuyu; Feng, Xia; Wu, Xiaodan; Liu, Zimeng; Zhang, Hufei; Liu, Xinhe
Abstract : Background . The aim of this study was to detect the effect of the laryngeal mask airway (LMA) versus the endotracheal tube (ETT) on postoperative nasal bleedings in and outside the operation room (OR) after intranasal surgery. Methods . 134 patients undergoing elective intranasal surgeries were randomly allocated to receive LMA or ETT during general anesthesia. The incidence, episodes, and severity of nasal bleeding were evaluated in the OR and within the postoperative 24 hours in the ward. Furthermore, medical assistance and severe complications were assessed. Results . The overall incidence of postoperative nasal bleeding throughout the observation period was similar between the two groups. The LMA reduced nasal bleeding in the OR. However, outside the OR, the incidence of the first episode of postoperative nasal bleeding in the LMA group was higher than that in the ETT group (difference: −26.5%; 95% CI: −42.2% to −10.7%; P < 0.001 ). In the LMA group, more patients needed medical assistance (P = 0.029 ), and the number of assistance was also higher (P = 0.027 ) in the ward. No severe complications occurred during the observation period. Conclusion . The LMA does not alleviate nasal bleeding conditions and even increases the demands of medical service outside the OR after intranasal surgery, although it reduces epistaxis during extubation.